2020
DOI: 10.1002/we.2576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil–structure interaction on the design of tuned mass damper to control the seismic response of wind turbine towers with gravity base

Abstract: This paper studies the effect of soil–structural interaction (SSI) on gravity‐based wind turbine towers equipped with tuned mass dampers (TMDs) subjected to earthquake loading. A small‐scale shaking table test of wind turbine towers with TMD was conducted, and the results showed that using TMD designed considering SSI resulted in larger vibration suppression. A simplified analytical numerical model was developed for SSI analysis considering TMD. The effect of soil site class and the earthquake intensity on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It has been found that multiple TMDs located at points of large modal amplitudes provide promising results for load mitigation when a wind turbine tower is subjected to the combined wind-waveearthquake loads [121]. Moreover, the soil-structure interaction should not be ignored in the efficient design of TMDs, since the flexibility of the soil could decrease the frequency of the structure by up to 25% [122,123]. Even though a TMD system is relatively simple, its untoward operation is very possible with a combination of multiple dampers, influencing the effectiveness of the control process.…”
Section: Tuned Mass Dampers (Tmds)mentioning
confidence: 99%
“…It has been found that multiple TMDs located at points of large modal amplitudes provide promising results for load mitigation when a wind turbine tower is subjected to the combined wind-waveearthquake loads [121]. Moreover, the soil-structure interaction should not be ignored in the efficient design of TMDs, since the flexibility of the soil could decrease the frequency of the structure by up to 25% [122,123]. Even though a TMD system is relatively simple, its untoward operation is very possible with a combination of multiple dampers, influencing the effectiveness of the control process.…”
Section: Tuned Mass Dampers (Tmds)mentioning
confidence: 99%
“…In order to enhance the seismic resilience of wind turbines, recently, the adaptation of active and passive control technologies such as tuned mass dampers (TMD), tuned sloshing dampers and tuned liquid dampers to wind turbines have been motivated in research on wind turbines. Dai et al [14] reported from experimental tests that the vibration control of TMDs depends on both soil stiffness and the frequency content of ground motion. Chen et al, [15] presented a multiobjective optimization methodology for a TMD and concluded good results of mitigation the seismic response of a wind turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with semiactive and active control techniques, 4,5 passive control methods, which do not require energy input, have been more commonly adopted to mitigate WT responses. Tuned mass dampers (TMDs), [6][7][8][9][10] tuned liquid dampers (TLDs), [11][12][13] tuned liquid column dampers (TLCDs), 14,15 rolling ball vibration absorbers, [16][17][18] pendulum TMDs, 19,20 and viscous dampers 21 have been proposed to control undesired vibrations of the towers, and their effectiveness was examined either numerically [6][7][8]14,[19][20][21] or experimentally. [9][10][11][12][13][15][16][17][18] Moreover, Larsen et al 22 used an electromagnetic shunted transducer to replace the traditional viscous dashpot in a pendulum absorber to control the wind-and sea wave-induced vibrations of the tower, and their results showed that an augmented pendulum absorber slightly improved the vibration damping effect with slightly larger damper stroke compared with the classic pendulum absorber.…”
mentioning
confidence: 99%